1992
DOI: 10.1083/jcb.119.5.1163
|View full text |Cite
|
Sign up to set email alerts
|

Cytosol- and clathrin-dependent stimulation of endocytosis in vitro by purified adaptors.

Abstract: Abstract. Using stage-specific assays for receptormediated endocytosis of transferrin (-Tfn) into perforated A431 cells we show that purified adaptors stimulate coated pit assembly and ligand sequestration into deeply invaginated coated pits. Late events in endocytosis involving membrane fission and coated vesicle budding which lead to the internalization of Tfn are unaffected. AP2, plasma membrane adaptors, are active at physiological concentrations, whereas AP1, Golgi adaptors, are inactive. Adaptor-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
105
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(113 citation statements)
references
References 37 publications
(61 reference statements)
8
105
0
Order By: Relevance
“…To directly measure de novo coated pit assembly, assays are performed in the presence of limiting concentrations of cytosol supplemented with purified adaptor proteins. When perforated A431 cells are incubated under these conditions adaptors specifically stimulate coated pit assembly which increases the extent of sequestration of BSST into deeply invaginated pits (Smythe et al, 1992b). Thus, adaptor-stimulated sequestration of BSST provides a measurement of the de novo assembly of functionally active coated pits (Smythe et al, 1992b).…”
Section: Sensitive Elisa-based Assays For Coated Pit Assembly Invagimentioning
confidence: 99%
See 4 more Smart Citations
“…To directly measure de novo coated pit assembly, assays are performed in the presence of limiting concentrations of cytosol supplemented with purified adaptor proteins. When perforated A431 cells are incubated under these conditions adaptors specifically stimulate coated pit assembly which increases the extent of sequestration of BSST into deeply invaginated pits (Smythe et al, 1992b). Thus, adaptor-stimulated sequestration of BSST provides a measurement of the de novo assembly of functionally active coated pits (Smythe et al, 1992b).…”
Section: Sensitive Elisa-based Assays For Coated Pit Assembly Invagimentioning
confidence: 99%
“…Extensive biochemical and morphological characterization of this assay system (Smythe et al, 1989; Schrnid and Smythe, 1991;Smythe et al, 1992b) has shown that coated vesicles which form during the in vitro reaction are largely derived from pre-existing coated pits. As a result, MesNaresistance selectively measures late events which correspond to coated vesicle budding and lead to the internalization of BSST.…”
Section: Sensitive Elisa-based Assays For Coated Pit Assembly Invagimentioning
confidence: 99%
See 3 more Smart Citations